Legal frameworks and specialized institutional frameworks for the social and solidarity economy in Latin America - Juan Pablo Martín; Mario Radrigán; Dalia Borge; Hugo Jácome; Leandro Pereira; Marietta Bucheli; Juan José Rojas; Mario Schujman (CEPAL Review, 2023)
This article analyses recent changes in social and solidarity economy (SSE) policies in eight Latin American countries: Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Mexico and Uruguay. It outlines the institutional rules that limited or added to States’ policymaking capacity, as well as examining progress on legislation and regulations and changes in specialized institutional frameworks. The information was obtained through an extensive review of documents and databases produced by government and academic institutions and social and solidarity economy organizations. The conclusion reached is that the concept has multiple interpretations, with specific characteristics in each country, and that it is being shaped and developed continuously. The article covers the different policy approaches to the social and solidarity economy, as reflected in legal frameworks, and also whether specialized institutional frameworks exist in the cases analysed.